2021
DOI: 10.1542/peds.2020-023432
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Severe SARS-CoV-2 Infection

Abstract: BACKGROUND: Initial reports on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in children suggested that very young age and comorbidities may increase risk of severe evolution, but these findings remained to be confirmed. We aimed to analyze the clinical spectrum of hospitalized pediatric SARS-CoV-2 infection and predictors of severe disease evolution. METHODS: We conducted a French national prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
115
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(144 citation statements)
references
References 35 publications
17
115
3
3
Order By: Relevance
“…[1][2][3][4] However, a subset of children present with severe multisystem inflammation associated with current or recent SARS-CoV-2 infection or COVID-19 exposure in the weeks before. [5][6][7][8][9][10] In the United States, this condition has been termed multisystem inflammatory syndrome in children (MIS-C). 11 While data have been published on the epidemiological characteristics and clinical spectrum of MIS-C, 5,[12][13][14][15][16][17] information on incidence of MIS-C is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, a subset of children present with severe multisystem inflammation associated with current or recent SARS-CoV-2 infection or COVID-19 exposure in the weeks before. [5][6][7][8][9][10] In the United States, this condition has been termed multisystem inflammatory syndrome in children (MIS-C). 11 While data have been published on the epidemiological characteristics and clinical spectrum of MIS-C, 5,[12][13][14][15][16][17] information on incidence of MIS-C is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Since December 2019, this virus was responsible for a pandemic that reached more than 100 million people and caused 2.3 million deaths worldwide as of February 2021 1 . Children are less often affected than adults and have exceptionally severe illness (1)(2)(3)(4). At the beginning of the pandemic, the disease was assumed to be transmitted mainly via children, as observed during influenza epidemics; school closures proved effective in limiting the spread of the disease (5).…”
Section: Introductionmentioning
confidence: 99%
“…All of these drawbacks were even greater in low-income families (17). In this context, France made many efforts to keep schools open even with high viral circulation 3 . Until high COVID-19 vaccination coverage is reached with a vaccinated population of all ages, other effective measures should be implemented to limit the spread of the epidemic among children who are often asymptomatic carriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, preliminary reports suggested that severe pediatric COVID-19 cases were more frequent in younger infants (<1 year of age; Gotzinger et al, 2020;Liu et al, 2020;Yang et al, 2020a), however, recent reports did not confirm this trend. COVID-19 severity in children seems to be associated with age ≥ 10 years, hypoxemia, obesity, and one or more underlying medical conditions (Bellino et al, 2020;Dong et al, 2020;Shekerdemian et al, 2020;Feldstein et al, 2021;Fernandes et al, 2021;Ouldali et al, 2021).…”
Section: Covid-19 In Childrenmentioning
confidence: 99%